The Young Turks in opposition - Hanioğlu, M. Şükrü (Studies in Middle Eastern history (New York, N.Y.), 1995)
A detailed study of the Turkish secret society known as CUP (Committee of Union and Progress), a movement which continues to influence the thinking of Turkish intellectuals. It also provides insights into diplomatic relations between the Ottoman Empire and Europe in the early 20th century.